Surgeon-Level Variability in Outcomes, Cost, and Comorbidity Adjusted-Cost for Elective Lumbar Decompression and Fusion. Issue 4 (14th June 2017) - Chotai, Silky; Sivaganesan, Ahilan; Sielatycki, John A; Archer, Kristin R; Call, Richard; McGirt, Matthew J; Devin, Clinton J
Abstract: BACKGROUND: The costs and outcomes following degenerative spine surgery may vary from surgeon to surgeon. Patient factors such as comorbidities may increase the health care cost. These variations are not well studied. OBJECTIVE: To understand the variation in outcomes, costs, and comorbidity-adjusted cost for surgeons performing lumbar laminectomy and fusions surgery. METHODS: A total of 752 patients undergoing laminectomy and fusion, performed by 7 surgeons, were analyzed. Patient-reported outcomes and 90-d cost were analyzed. Multivariate regression model was built for high-cost surgery. A separate linear regression model was built to derive comorbidity-adjusted 90-d costs. RESULTS: No significant differences in improvement were found across all the patient-reported outcomes, complications, and readmission among the surgeons. In multivariable model, surgeons #4 ( P < .0001) and #6 ( P = .002) had higher odds of performing high-cost fusion surgery. The comorbidity-adjusted costs were higher than the actual 90-d costs for surgeons #1 ( P = .08), #3 ( P = .002), #5 ( P < .0001), and #7 ( P < .0001), whereas they were lower than the actual costs for surgeons #2 ( P = .128), #4 ( P < .0001), and #6 ( P = .44). CONCLUSION: Our study provides valuable insight into variations in 90-d costs among the surgeons performing elective lumbar laminectomy and fusion at a single institution. Specific surgeons were found to have greater odds of performing high-cost surgeries. Adjusting for preoperative comorbidities, however, led to costs that were higher than the actual costs for certain surgeons and lower than the actual costs for others. Patients' preoperative comorbidities must be accounted for when crafting value-based payment models. Furthermore, designing intervention targeting "modifiable" factors tied to the way the surgeons practice may increase the overall value of spine care.